2014
DOI: 10.1128/aac.01483-13
|View full text |Cite
|
Sign up to set email alerts
|

Structural Origins of Oxacillinase Specificity in Class D β-Lactamases

Abstract: cSince the discovery and use of penicillin, the increase of antibiotic resistance among bacterial pathogens has become a major health concern. The most prevalent resistance mechanism in Gram-negative bacteria is due to ␤-lactamase expression. Class D ␤-lactamases are of particular importance due to their presence in multidrug-resistant Acinetobacter baumannii and Pseudomonas aeruginosa. The class D enzymes were initially characterized by their ability to efficiently hydrolyze isoxazolyl-type ␤-lactams like oxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…30 Secondly, in both OXA-23 and OXA-24/40 the proline in question is found in a loop that borders the active site and has been implicated in the modulation of both substrate selectivity and catalytic activity for diverse classes of antibiotics. 10, 12, 13, 17 De Luca et al noted the presence of this proline in a sequence motif typically associated with class D carbapenemases. 10 Lastly, the study that identified OXA-160 ( i.e .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…30 Secondly, in both OXA-23 and OXA-24/40 the proline in question is found in a loop that borders the active site and has been implicated in the modulation of both substrate selectivity and catalytic activity for diverse classes of antibiotics. 10, 12, 13, 17 De Luca et al noted the presence of this proline in a sequence motif typically associated with class D carbapenemases. 10 Lastly, the study that identified OXA-160 ( i.e .…”
Section: Resultsmentioning
confidence: 99%
“…10, 12, 13, 17 The proline, however, resides near the point where the loop reenters the enzyme core as strand β6, and is thus unlikely to make any direct contacts with substrates. This, and the fact that proline’s unique structural properties would be altered upon conversion to serine, suggested to us that the mutation may lead to extensive structural rearrangements of the β5-β6 loop and thus affect substrate binding indirectly.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations